A rebellion of Chinese coolies: Pativilca, 1870 - Rodríguez, Humberto (1978)
In the month of September 1870 there was a rebellion of Chinese coolies that extended to several haciendas in the Pativilca valley. It all started at the Araya hacienda in the middle part of the valley, and quickly spread to other farms. Initially there were one hundred Chinese rebels. After twelve hours the Asians numbered between 1,200 and 1,500. The objective of the rebels was the same in all the haciendas where the revolt broke out.